Edward MacDowell's European piano music : the forging of an American composer - Bertagnolli, Paul, 1956- (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Edward MacDowell's European Piano Music is a critical study of the piano music that MacDowell composed during his European sojourn (1876-1888), steeped in reception history and with a special emphasis of programmaticism. The book expands current knowledge of MacDowell's childhood in four chapters based on his previously uninvestigated sheet music collection, thereby achieving a better balance among the stages of MacDowell's life than is evident in most books of the life-and-works variety. Prolific contemporaneous music criticism, meticulously preserved in MacDowell's scrapbooks, is likewise undervalued in the MacDowell literature, but it furnishes penetrating observations about the expressive and programmatic content of numerous compositions, especially as it was revealed to critics when MacDowell performed his own works. Lastly, the book offers explanations for why MacDowell immersed himself in European culture for decades and then, at a crucial juncture in his career, embraced diverse American heritages and worked toward a conception of a pluralistic music that was American "in a creative sense." The book's content and methodology would appeal most directly to specialists within the broad fields of musicology and music theory, particularly within American art music and its composers; nineteenth century music; program music; reception history; and piano literature"--
The sheet music collection of Walter and Eddie McDowell : provenance, contents, cosmopolitanism -- The collection and Eddie's teachers : Buitrago, Desvernine, Carreño -- The sheet music collection's compositional impact -- "Untold gold" : taking the juvenilia seriously -- Leaving Paris, finding a vocation in Germany -- "Modernity" in MacDowell's first three published piano works -- The transatlantic first piano concerto -- Frankfurt character pieces : forgotten narratives -- Wiesbaden character pieces : literary and theatrical embodiments -- The Shakespearean second piano concerto.
Keywords: MacDowell, Edward, -- 1860-1908 -- Criticism and interpretation; MacDowell, Edward, -- 1860-1908.; Piano music -- History and criticism; Program music; MUSIC / Genres & Styles / Classical; MUSIC / History & Criticism